FORWARD GUIDANCE CONTRACTS. (December 2019) - Gersbach, Hans; Hahn, Volker; Liu, Yulin
Abstract : We examine "Forward Guidance Contracts, " which penalize central bankers for choosing high interest rates. We integrate those contracts into the New Keynesian Framework and show that they can be used to overcome a liquidity trap. Moreover, although the government takes only a share of the social benefits into account when it has to decide whether to offer the contract, we demonstrate that for plausible parameter values the government will always find it desirable to offer the contract in a liquidity trap but not in normal times. Finally, we show that the optimal duration of such contracts is typically very short.